On the performance of existing acoustic energy models when applied to multi-purpose performance halls. (October 2020) - Gao, Jianliang; Tang, S.K.; Zhao, Yuezhe; Cai, Yangsheng; Pan, Lili
Highlights: Measurements were carried out in two multi-purpose performance halls. Results are compared with existing acoustic energy model predictions. The best model considers direct sound arrival and onset of reverberant sound decay. Inaccurate estimation of energy ratios is due to error in estimating late energy. Abstract: Acoustical measurements were done in two multi-purpose performance halls in the present study. The measured data are compared with predictions from three acoustic energy models in existing literature derived for churches and large reverberant theatres. Results show that the model suitable for the present multi-purpose performance halls is the one which takes into account the time difference between direct sound arrival and onset time of reverberant sound decay. However, unlike the church cases, the time difference appears to have no direct definite relationship with the source-receiver distance alone. A method for the prediction of time difference is then proposed for multi-purpose performance hall application. In addition, the prediction of the late reflected energy is not satisfactory, and this deficiency is the main problem leading to the inaccurate estimation of clarity, definition and centre time in the present study.